Formulation of Criminal Law Policy for Distribution of Non-Food Animal Meat for Consumption - Nahdiya Sabrina (Faculty of Law, University of Merdeka Malang, 2023)
This study aims to provide an analysis of the many cases of distribution of non-food animal meat for consumption purposes that have recently received attention, such as the rampant sale of cat and dog meat which often occurs in society. Cats and dogs are pets kept by humans. These animals are not included in the consumption of livestock. Consumption of non-food animals is a heinous act that can become a zoonotic vector. This study uses normative legal research methods with several approaches, namely the statutory approach and the conceptual approach. The results obtained are that there are laws and regulations related to the distribution of non-food animal meat for consumption purposes, but some of these regulations do not mention the imposition of sanctions on the distribution of non-food animal meat for consumption purposes. Criminal laws should provide for the torture of animals and the distribution of non-food animal meat for consumption and sanctions. This is considering the dangers of consuming non-food animals which have the potential to harm the wider community.How to cite item: Sabrina, Nahdiya. â€œFormulation of Criminal Law Policy for Distribution of Non-Food Animal Meat for Consumption.â€ Jurnal Cakrawala Hukum. 14 no. 1 (2023): 28-35. DOI: 10.26905/idjch.v14i1.10049.